2012
DOI: 10.1186/1556-276x-7-254
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-fiber tips for scanning probe microscopes and molecular electronics experiments

Abstract: We fabricate and characterize carbon-fiber tips for their use in combined scanning tunneling and force microscopy based on piezoelectric quartz tuning fork force sensors. An electrochemical fabrication procedure to etch the tips is used to yield reproducible sub-100-nm apex. We also study electron transport through single-molecule junctions formed by a single octanethiol molecule bonded by the thiol anchoring group to a gold electrode and linked to a carbon tip by the methyl group. We observe the presence of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…It is worth commenting the connection between our results and the experiments of Castellanos-Gomez 15,39 where molecular junctions were formed between carbon tips and octanethiol self-assembled monolayers. In those experiments, the appearance of rather short plateaus was reported, which was tentatively attributed to the formation of a chemical bond between the tip and the non-thiolated end of the molecule.…”
Section: All-carbon Single-molecule Junctionssupporting
confidence: 75%
“…It is worth commenting the connection between our results and the experiments of Castellanos-Gomez 15,39 where molecular junctions were formed between carbon tips and octanethiol self-assembled monolayers. In those experiments, the appearance of rather short plateaus was reported, which was tentatively attributed to the formation of a chemical bond between the tip and the non-thiolated end of the molecule.…”
Section: All-carbon Single-molecule Junctionssupporting
confidence: 75%
“…Despite their chemical stability and electrical properties, there are few examples of carbon fiber tips used as STM and/or AFM probe which have been reported in the literature [32][33][34][35][36][37]. Recently, Castellanos Gomez et al [32,34,35] presented results obtained with carbon fiber tips in an AFM/STM system. Atomic resolution was achieved on a freshly cleaved surface of highly oriented pyrolytic graphite in constant height STM mode.…”
Section: Introductionmentioning
confidence: 96%
“…However Mousa investigated the field electron emission (FEE) properties of electrochemically etched carbon fiber tips, and found that the tip apex radius was below 100 nm [29]. Despite their chemical stability and electrical properties, there are few examples of carbon fiber tips used as STM and/or AFM probe which have been reported in the literature [32][33][34][35][36][37]. Recently, Castellanos Gomez et al [32,34,35] presented results obtained with carbon fiber tips in an AFM/STM system.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Quanto a ponta de prova, temos exemplo de pontas de tungstênio ou platina-irídio, regularmente usadas em STM [38], fibras óticas [14], cantilevers regulares de AFM [19], e, mais recentemente, pontas baseadas em carbono, como fibras e nanotubos de carbono [24,56,57]. Para aplicação do QTF em AFM, existem dois modos principais.…”
Section: O Uso Do Qtf Em Afmunclassified